Prehabilitation programs – a systematic review of the economic evidence - Ke, Yuhe; Ng, Roderica Rui Ge; Elangovan, Shalini; Leong, Yun Hao; Goh, Zhao Han; Graves, Nicholas; Shannon, Nicholas B.; Abdullah, Hairil Rizal (Frontiers in Medicine, 2023)
Introduction Prehabilitation, which involves improving a patient's physical and psychological condition before surgery, has shown potential benefits but has yet to be extensively studied from an economic perspective. To address this gap, a systematic review was conducted to summarise existing economic evaluations of prehabilitation interventions. Methods The PRISMA Protocols 2015 checklist was followed. Over 16,000 manuscripts were reviewed, and 99 reports on preoperative interventions and screening tests were identified, of which 12 studies were included in this analysis. The costs are expressed in Pounds (GBP, £) and adjusted for inflation to December 2022. Results The studies were conducted in Western countries, focusing on specific surgical subspecialties. While the interventions and study designs varied, most studies demonstrated cost savings in the intervention group compared to the control group. Additionally, all cost-effectiveness analysis studies favoured the intervention group. However, the review also identified several limitations. Many studies had a moderate or high risk of bias, and critical information such as time horizons and discount rates were often missing. Important components like heterogeneity, distributional effects, and uncertainty were frequently lacking as well. The misclassification of economic evaluation types highlighted a lack of knowledge among physicians in prehabilitation research. Conclusion This review reveals a lack of robust evidence regarding the economics of prehabilitation programs for surgical patients. This suggests a need for further research with rigorous methods and accurate definitions.